El factor de la precipitación en la formación de avenidas en la cuenca alta del Turia - Morell Cuevas, Jonatan (Geographicalia, 2016)
Hydrological research are unusually from geography in Spain. A particular aspect of hydrology is analysed in the high Turia drainage basin (Teruel). The principles events of floods has been individualized in the different measurement points of the head drainage basin. Morphological aspects and principles characteristics are more analysed. Also, meteorological aspects like precipitation and synoptic situation. Finally, we connect both analysis in order to establish how is the transformation precipitation-runoff, elements affecting and volumetric analysis. Risk and hydrological resource are too valorised.